Work and Artifact. Aristotelian–Heideggerian Meditation - Sverdiolas, Arūnas (Problemos, 2007)
As a continuation of the previous analysis of the mechanism of culture, performed employing the paradigmatic actions of establishing social existence fundamentals and their preservation, the paper deals with a substantializing action such as artifact manufacture and artifact existence preservation. The arguments are based on the cornerstones of Western theoretical tradition (Aristotelian and Heideggerian con cepts of artifact and tool) in an attempt of their critical reconsideration (re-centering) and thus opening new perspectives of their interpretation in compliance with the modern pecularities of experiencing the origination, duration, dissipation and decay of artifacts.